PENGEMBANGAN MODEL PELATIHAN BERBASIS KINERJA UNTUK PENINGKATAN KOMPETENSI TUTOR PAKET C - Anan Sutisna (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
This research aimed at discovering a training model to improve the competence of Package C tutors. To meet the objective, the research developed a performance - based training model focusing on the tutor`s competence in conducting the instruction. The training model was developed based on the fact and consideration that the on going training process was regarded too conventional emphasizing cognitive aspects. The performance - based training model was developed applying research and development model. The result showed that this model is effective to improve the pedagogic and andragogic competence of Package C tutors in comunity learning activities center.